Single-Input Four-Output Current Mode Filter Using Operational Floating Current Conveyor - Neeta Pandey; Deva Nand; Zubair Khan (Active and Passive Electronic Components)
This paper presents operational floating current conveyor (OFCC) based single input four output current mode filter. It employs only three OFCCs and two grounded capacitors and resistors each. The MOS based grounded resistors implementation is used, which adds feature of electronic tunability to the filter parameters. The filter also enjoys low component spread and low sensitivity performance. The effect of finite transimpedance and parasites of OFCC on the proposed circuit is also analyzed. The functionality of the proposed circuit is demonstrated through SPICE simulations using 0.5 µm CMOS process model provided by MOSIS (AGILENT).